Avaliação do Ciclo de Vida no contexto da economia circular de pellets e briquetes produzidos na América Latina - Matheus, Thiago Teixeira (2022)
Biomass is considered an underused energy source in several regions of the world, although there are optimistic market projections for the next years. Local generation of residual biomass can supply part of the energy demand in some regions of Latin America and can also be exported as pellets and briquettes. However, the environmental performance of these solid biofuels should be further investigated from the perspective of the Circular Economy (CE), mostly due to the environmental impacts associated with their exportation and the saving of virgin raw material resulting from the use of residual biomass. In this sense, this dissertation consisted of on the analysis of the environmental performance of pellets and briquettes through the combination of Life Cycle Assessment (LCA) with the recent Circular Footprint Formula (CFF) method, being this integration an important strategy to promote sustainable production. Eleven case studies were modeled in a cradle-to-product-distribution approach, all of them related to pellets and briquettes produced with different biomass sources in Brazil, Chile, Colombia and Mexico, and their exportation to European market. The Functional Unit (FU) equivalent to 1 MJ of energy embedded in the biomass pellets and briquettes was adopted. The impacts related to the Global Warming Potential (GWP), Acidification Potential (AP), Eutrophication Potential (EP), Abiotic Depletion Potential (ADPe), Ozone Layer Depletion Potential (ODP) and Photochemical Ozone Creation Potential (POCP) by the CML method, and the Non-Renewable Cumulative Energy Demand (CED) for the FU was also calculated. The CFF allocation method was applied based on the results of LCA, and the results compared with and without the CFF use. The results pointed to the low carbon footprint of the pellets and briquettes in view of the absorption of biogenic carbon associated with the land use by the raw material sources, and because they represent residual biomass. The amount of biomass demanded by the pellets and briquettes production can avoid the emission of up to 287 g CO2-eq per MJ of generated energy. However, exporting to Europe significantly increases emissions and impacts across all impact categories analyzed, with road and sea transport stages representing important lifecycle hotspots across all eleven case studies, mostly for ADPe, AP, ODP and CED. The application the CFF revealed that this method requires some adaptations when applied in the context of pellets and briquettes, which means important practical limitations. Furthermore, the integration of CE with LCA enhances the environmental savings of residual biomass pellets and briquettes due to the avoided impacts in all the impact categories associated with the increasing circularity by avoiding virgin wood and demanding residual biomass instead.